Competitiveness and Economic Growth in the European Union - ZAGORŠEKOVÁ, Natália; ČIEFOVÁ, Michaela; ČAMBALÍKOVÁ, Andrea (Journal of Advanced Research in Law and Economics, 2018)
The paper focuses on competitiveness at the national level and on the impact of competitiveness on economic growth. We look at the relationship between competitiveness and economic growth based on the data from the European Union member states. The competitiveness of the economies is measured by the Global Competitiveness Index, which is published by the World Economic Forum. The European Union member states show significant differences in competitiveness. In the sample examined, the positive relationship between the level of competitiveness and economic growth was not confirmed.